2021
DOI: 10.1071/wf21004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting black spruce fuel characteristics with Airborne Laser Scanning (ALS)

Abstract: Wildfire decision support systems combine fuel maps with other fire environment variables to predict fire behaviour and guide management actions. Until recently, financial and technological constraints have limited provincial fuel maps to relatively coarse spatial resolutions. Airborne Laser Scanning (ALS), a remote sensing technology that uses LiDAR (Light Detection and Ranging), is becoming an increasingly affordable and pragmatic tool for mapping fuels across localised and broad areas. Few studies have used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Their regression model validation produced RMSEs of 0.27 (R 2 = 0.84) and 0.024 (R 2 = 0.88) while including 101 and 57 field sampling locations, respectively. Cameron et al [30] reported a RMSE of 0.098 (R 2 = 0.78) whilst using 52 training samples. Considering the low number of samples in the present study, a RMSE of 0.069 (R 2 = 0.73) was acceptable, especially as CBD is only one of multiple components of the FH assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their regression model validation produced RMSEs of 0.27 (R 2 = 0.84) and 0.024 (R 2 = 0.88) while including 101 and 57 field sampling locations, respectively. Cameron et al [30] reported a RMSE of 0.098 (R 2 = 0.78) whilst using 52 training samples. Considering the low number of samples in the present study, a RMSE of 0.069 (R 2 = 0.73) was acceptable, especially as CBD is only one of multiple components of the FH assessment.…”
Section: Discussionmentioning
confidence: 99%
“…LiDAR-derived metrics produced for this analysis include several basic descriptive statistics that have been proven useful when modeling vertical structure for forestry applications [21,[29][30][31]. A large portion of the metrics (>60%) is related to the height values of laser returns (Z-dimension).…”
Section: Lidarmentioning
confidence: 99%
“…The relatively short stature of natural boreal conifer forests [55,66] means that maximum achievable CBH through pruning is limited in comparison with species such as ponderosa pine (Pinus ponderosa) and Douglas fir (Pseudotsuga menziesii), which are characterized by substantially higher tree heights [67]. It is also noteworthy that in mature stands represented by the C-2 fuel type, black spruce tree crowns can extend nearly to the ground, such that thinning alone cannot be relied upon to elevate CBH.…”
Section: Canopy Base Height (Cbh)mentioning
confidence: 99%
“…The sensitivity of crown fire initiation predictions to assumptions about surface fuel load and surface fuel consumption is illustrated in Figure 4 for fuel-treated black spruce stands at the Pelican Mountain research site in Alberta. Given the field-measured mean CBH of 3.45 m documented by Cameron [55] and assuming 100% foliar moisture content, Van Wagner and Byram models indicate that surface fuel consumption ≤ 0.72 kg/m 2 would be required to inhibit crown fire development under relatively low surface fire spread rates of ≤ 5 m/min, which would drop to fuel consumption thresholds of ≤ 0.36 kg/m 2 and ≤ 0.24 kg/m 2 for inhibiting crown fires at rates of spread of 10 and 15 m/min, respectively.…”
Section: Model Sensitivity To Assumptions-illustrative Examplesmentioning
confidence: 99%
See 1 more Smart Citation